Physicochemical, Microbiological, Antimicrobial, and Sensory Characteristics of Postbiotic Yogurt Enriched with Parijoto Fruit (Medinilla speciosa) Puree - Pranata, Jony; Hasana, Zahriatus Yuta Laila; Rahima, Ghianaya Fauza; Kurniawan, Adif; Dewi, Cecilia Shinta; Saleha, Rischa Amalia (Faculty of Animal Science Universitas Brawijaya, 2026)
Postbiotic yogurt has emerged as a functional dairy product suitable for consumers who cannot tolerate live probiotics. The addition of natural bioactive-rich ingredients, such as parijoto fruit (Medinilla speciosa), may enhance its quality and functionality. This study aimed to evaluate the effect of parijoto fruit puree on the physicochemical, microbiological, antimicrobial, color, and sensory properties of postbiotic yogurt. The research was conducted from August to September 2025 using an experimental laboratory method with a Completely Randomized Design (CRD). Five levels of parijoto puree were applied: 0%, 5%, 10%, 15%, and 20%, each with four replications, resulting in 20 experimental units. Postbiotic yogurt was produced from fresh cow’s milk fermented with Lactobacillus bulgaricus and Streptococcus thermophilus, followed by thermal inactivation. Parameters observed included pH, moisture, protein, fat, viscosity, total acidity, total lactic acid bacteria (LAB), color characteristics (L*, a*, b*), antimicrobial activity against Escherichia coli and Salmonella typhi, and sensory attributes (taste, color, aroma, and thickness). Data were analyzed using ANOVA followed by Duncan’s Multiple Range Test. The results showed that parijoto puree significantly affected moisture content, total LAB, color parameters, total acidity, fat content, and sensory attributes of taste, color, and aroma (p < 0.01), but had no significant effect on pH, protein content, viscosity, thickness, or antimicrobial activity (p > 0.05). Higher concentrations reduced LAB counts and fat content, increased acidity, and darkened color. In conclusion, parijoto puree has potential as a functional ingredient, but its concentration must be optimized.